Against Divisiveness: Digital Workers of the World Unite! A Rejoinder to César Bolaño and Eloy Vieira. (January 2015) - Fuchs, Christian
This piece is a short rejoinder to César Bolaño and Eloy Vieira's paper The Political Economy of the Internet and related articles (e.g., Comor, Foley, Huws, Reveley, Rigi and Prey, Robinson) that center around the relevance of Marx's labor theory of value for understanding social media. I argue that Dallas Smythe's assessment of advertising was made to distinguish his approach from the one by Baran and Sweezy. Smythe developed the idea of capital's exploitation of the audience at a time when both feminist and anti-imperialist Marxists challenged the orthodox idea that only white factory workers are exploited. The crucial question is how to conceptualize productive labor. This is a theoretical, normative, and political question. A mathematical example shows the importance of the "crowdsourcing" of value-production on Facebook. I also point out parallels of the contemporary debate to the Soviet question of who is a productive or unproductive worker in the Material Product System.